Leveraging identity and access management technology to accelerate emergency COVID-19 vaccine delivery - George A. Gellert (SAGE Publishing, 2023)
COVID-19-related vaccine demand and delivery volume challenged delivery organizations as few crises have. Imperatives to ensure security of patient information, defend against cybersecurity threats, and accurately identify/authenticate clinician identity for patients remained unchanged. Deployment of identity access and management (IAM) and single sign-on (SSO) can accelerate operationalization of a vaccine delivery center when urgently needed in a crisis. Innovative application of existing IAM/SSO technology, combined with an identity governance solution, greatly accelerated vaccine delivery. Secure access enabled by IAM technology facilitated a rapid expansion (25 minutes) where 500 new vaccine delivery personnel were identified and authenticated during a period of high pandemic incidence. Existing digital identity solutions enabled a vaccine delivery organization to accelerate secure IAM of clinical staff during the peak of the COVID-19 pandemic. Existing IAM investments and capabilities that are widely implemented in nations with mature health information technology systems can greatly accelerate standing up emergent vaccine delivery capabilities and sites in the midst of a public health crisis.